Aerodynamic Performance and Surface Flow Structures of Leading-Edge Tubercled Tapered Swept-Back Wings - Wei, Zhaoyu (2018)
Effects of leading-edge tubercles on the aerodynamic performance and surface flow structures for tapered swept-back wings have been determined experimentally across a range of Reynolds numbers (Re). The orientation of SD7032 profile and tubercles were also particularly evaluated at Re=2.2×105. Lift and drag curve behavior of the baseline wing with SD7032 airfoil profile aligned in the streamwise direction do not vary significantly when Reynolds number exceeds Re=8.2×104. Results also indicate that the gross surface flow structures are not too sensitive towards the orientation of the SD7032 airfoil profile and tubercles. Nevertheless, compared with its baseline counterpart, the wing with tubercles normal to the leading-edge can slightly enhance the aerodynamic performance over a lower angle-of-attack (AOA) range of 2°<α<7°. The two different tubercle orientations are also observed to improve stall behavior with lift enhancements and drag reductions at AOAs larger than 20°. Surface flow patterns show that highly complicated surface vortex structures and regular critical points are produced at moderate AOAs, where the distribution of critical points is dependent upon the leading-edge tubercle orientation and presence of sweep-angle. Surface vortices are revealed to either modify the laminar separation bubbles (LSBs) or disrupt large-scale recirculating region at smaller or larger AOAs respectively. At moderate AOAs however, surface vortices produced downstream of troughs are speculated to lead to poor drag performance.